Association between pulmonary artery pulsatility and mortality after implantation of left ventricular assist device - Ali Akamkam; Vincent Galand; Marie Jungling; Clément Delmas; Camille Dambrin; Mathieu Pernot; Michel Kindo; Philippe Gaudard; Philippe Rouviere; Thomas Senage; Olivier Chavanon; Marylou Para; et al. (ESC Heart Failure, 2024)
Abstract Aims Right ventricular failure after left ventricular assist device (LVAD) implantation is a major concern that remains challenging to predict. We sought to investigate the relationship between preoperative pulmonary artery pulsatility index (PAPi) and mortality after LVAD implantation. Methods and results A retrospective analysis of the ASSIST‐ICD multicentre registry allowed the assessment of PAPi before LVAD according to the formula [(systolic pulmonary artery pressure − diastolic pulmonary artery pressure)/central venous pressure]. The primary endpoint was survival at 3 months, according to the threshold value of PAPi determined by the receiver operating characteristic (ROC) curve. A multivariate analysis including demographic, echographic, haemodynamic, and biological variables was performed to identify predictive factors for 2 year mortality. One hundred seventeen patients were included from 2007 to 2021. The mean age was 58.45 years (±13.16), with 15.4% of women (sex ratio 5.5). A total of 53.4% were implanted as bridge to transplant and 43.1% as destination therapy. Post‐operative right ventricular failure was observed in 57 patients (48.7%), with no significant difference between survivors and non‐survivors at 1 month (odds ratio 1.59, P = 0.30). The median PAPi for the whole study population was 2.83 [interquartile range 1.63–4.69]. The threshold value of PAPi determined by the ROC curve was 2.84. Patients with PAPi ≥ 2.84 had a higher survival rate at 3 months [PAPi < 2.84: 58.1% [46.3–72.8%] vs. PAPi ≥ 2.84: 89.1% [81.1–97.7%], hazard ratio (HR) 0.08 [0.02–0.28], P < 0.01], with no significant difference after 3 months (HR 0.67 [0.17–2.67], P = 0.57). Other predictors of 2 year mortality were systemic hypertension (HR 4.22 [1.49–11.97], P < 0.01) and diabetes mellitus (HR 4.90 [1.83–13.14], P < 0.01). LVAD implantation as bridge to transplant (HR 0.18 [0.04–0.74], P = 0.02) and heart transplantation (HR 0.02 [0.00–0.18], P < 0.01) were associated with a higher survival rate at 2 years. Conclusions Preoperative PAPi < 2.84 was associated with a higher risk of early mortality after LVAD implantation without impacting 2 year outcomes among survivors.